2022
DOI: 10.1002/hsr2.874
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of COVID‐19 mRNA vaccines in hemodialysis patients: Systematic review and meta‐analysis

Abstract: Background and Aims Vaccine response is a concern in hemodialysis patients. Given that hemodialysis patients were not included in clinical trials, we aimed to synthesize the available evidence on the immunogenicity of coronavirus disease 2019 (COVID‐19) mRNA vaccines in hemodialysis patients. Methods We searched Scopus, PubMed, Sciencedirect, and finally google scholar databases for studies on COVID‐19 mRNA‐vaccines immunogenicity in hemodialysis patients up to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In addition, as other authors have shown (El Karoui & De Vriese, 2022; Oliver & Blake, 2022), we found that vaccination reduced the need for hospital admission. Moreover, we found that the number of vaccine doses received influenced the presence or absence of symptoms, supporting recent findings that show that the clinical efficacy of COVID-19 vaccination in HD patients increases substantially with the number of doses (Ashby et al, 2022; Falahi et al, 2022; Hernández-Porto et al, 2022). Therefore, studies such as ours could contribute to encourage vaccination among the unvaccinated population by adding new evidence of its efficacy in clinical samples.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, as other authors have shown (El Karoui & De Vriese, 2022; Oliver & Blake, 2022), we found that vaccination reduced the need for hospital admission. Moreover, we found that the number of vaccine doses received influenced the presence or absence of symptoms, supporting recent findings that show that the clinical efficacy of COVID-19 vaccination in HD patients increases substantially with the number of doses (Ashby et al, 2022; Falahi et al, 2022; Hernández-Porto et al, 2022). Therefore, studies such as ours could contribute to encourage vaccination among the unvaccinated population by adding new evidence of its efficacy in clinical samples.…”
Section: Discussionsupporting
confidence: 90%
“…91 Since the COVID-19 pandemic has forced healthcare services and finances toward prevention strategies, including vaccination campaigns against this devastating viral infection, there are progressive concerns regarding the considerable disruptions in the control programs against various parasitic diseases, such as CL, and the subsequent rise in affected patients. 55,58 As Figure 15 Previous reports demonstrated the effectiveness of the rodent control program implementation, the retraining courses, and the implementation of health education programs for healthcare personnel and inhabitants of endemic regions in controlling CL. [62][63][64][65][66] Hence, establishing and empowering these actions could be recommended to control CL in Ilm County and other endemic regions.…”
Section: Discussionmentioning
confidence: 96%
“…So, CL could be a serious threat to pilgrims on these occasions 91 . Since the COVID‐19 pandemic has forced healthcare services and finances toward prevention strategies, including vaccination campaigns against this devastating viral infection, there are progressive concerns regarding the considerable disruptions in the control programs against various parasitic diseases, such as CL, and the subsequent rise in affected patients 55,58 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an increase in adverse pregnancy outcomes, such as preterm birth in women with COVID-19 compared to uninfected pregnant women, has been reported [ 11 , 14 , 15 ]. The likelihood of their neonates being hospitalized is also three times higher, although several vaccines and traditional and modern treatment platforms have been developed and evaluated for COVID-19[ [15] , [16] , [17] , [18] , [19] ]. While many studies have investigated neurological symptoms in adults with COVID-19, limited studies have yet been conducted on neurological morbidities in children exposed to COVID-19 in utero [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%